Artificial feeding and nutritional status of semi-domesticated reindeer during winter - Mauri Nieminen; Aune-Sinikka Pokka; Ulla Heiskari (Rangifer, 1987)
Three feeding experiments were done during 1980-82 with semi-domesticated reindeer in captivity out of doors in Northern Finland. Calves and adult hinds were fed with lichens (Cladina spp.), hay, dry molasses pulp and other feeds containing different amounts of proteins and other nutrients. The body weight, blood and faecal N were lowest in lichen fed groups. Slightly higher values were measured in groups fed with dry or ground hay, dry molasses pulp, oat bran and commercial feeds.